2015
DOI: 10.14737/journal.aavs/2015/3.9.485.490
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Poultry in Food Borne Salmonellosis and its Public Health Importance

Abstract: | Salmonella organisms are most frequently isolated bacterial agents of food borne outbreaks. Due to its economic importance and risks to human health, salmonellosis poses significant role in public health. Poultry serves as reservoir of Salmonella and poultry meat and eggs have been implicated in food associated outbreaks of salmonellosis. The presence of Salmonella in poultry makes the food chain unsafe from farm to the table. In this review, we explore various public health aspects of food borne salmonellos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
2
15
0
2
Order By: Relevance
“…In our study, all isolates serotyped S. Typhimurium were found positive for spy gene. The sensibility of the primer used in this study has also been also well demonstrated using simplex or multiplex PCR assays (Ahmed and Shimamoto, 2014;Can et al, 2014;Manoj et al, 2015).…”
Section: Distribution Of Salmonella Serovarssupporting
confidence: 68%
See 1 more Smart Citation
“…In our study, all isolates serotyped S. Typhimurium were found positive for spy gene. The sensibility of the primer used in this study has also been also well demonstrated using simplex or multiplex PCR assays (Ahmed and Shimamoto, 2014;Can et al, 2014;Manoj et al, 2015).…”
Section: Distribution Of Salmonella Serovarssupporting
confidence: 68%
“…It includes more than 2500 serovars that inhabit the gastrointestinal tracts of various domestic and wild animal species (Bahnass et al, 2015). It is estimated that salmonellosis represents 93.8 (16%) million cases of human gastroenteritis among an estimated 582 million cases of 22 different food borne enteric diseases, and it is responsible for 155 000 deaths worldwide each year (Elgroud et al, 2015;Manoj et al, 2015). Salmonella enterica subsp.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, egg and egg products are the important source of salmonellosis 1 . Unhygienic practice of farm handlers even home-made egg foods can cause salmonellosis due to ingestion of undercooked egg 10 .…”
Section: Transmission To Humanmentioning
confidence: 99%
“…Salmonella organisms are most frequently isolated bacterial agents of food borne disease outbreaks especially from poultry and are of significant public health concern 1 . Due to its significant morbidity and mortality rates salmonellosis causes risks to human health and economic loss 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Enteritidis and Typhimurium represent the most frequently Salmonella enterica subsp. enterica serotypes involved in both animal and human salmonellosis [1,3,[9][10][11]. Their vertical transmission is of lower importance in several European countries since the implementation of rigorous eradication programs at breeding level of the production chain.…”
Section: Introductionmentioning
confidence: 99%